A Population-Based Study of Peyronie's Disease: Prevalence and Treatment Patterns in the United States - Dana Britt DiBenedetti; Dat Nguyen; Laurie Zografos; Ryan Ziemiecki; Xiaolei Zhou (Advances in Urology)
Purpose. To estimate the US prevalence of Peyronie's disease (PD) from patient-reported data and to identify diagnosis and treatment patterns. Methods. 11,420 US males ≥18 years old completed a brief web-based survey regarding the presence of PD, past treatments, and penile symptoms (Phase 1). Phase 1 respondents with PD diagnosis, history of treatment, or PD-related symptoms then completed a disease-specific survey (Phase 2). Results. Estimated prevalence of PD ranged from 0.5% (diagnosis of PD) to 13% (diagnosis, treatment, or penile symptoms). Thirty-six percent of Phase 2 participants reported that penile symptoms interfered with sexual activities. Of participants who sought treatment for penile symptoms (𝑛=128), 73% initially saw a primary care physician, 74% did not receive treatment from their first doctor, and 92% were not diagnosed with PD. Conclusions. PD may be underdiagnosed/undertreated in the US. Improved awareness is needed of PD symptoms and treatment options among health care professionals.